1984
DOI: 10.2134/agronj1984.00021962007600030028x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Soybean Harvest Index1

Abstract: Previous work had indicated that the harvest index within cultivars of soybeans [Glycine max(L.) Merr.] might be fairly stable. Such stability of harvest index would greatly simplify the conceptualization of the influence of seed growth processes on yield. In the studies reported here harvest index of field‐grown soybean plants was measured in response to four types of environmental influence: interplant competition, extended photoperiod, timing of drought stress, and degrees of drought stress (line source irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
33
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(46 citation statements)
references
References 9 publications
10
33
1
Order By: Relevance
“…Therefore, HI may be stable except when the assimilate during the seed-fi lling period is strongly suppressed by low solar radiation in all cultivars used. Our results were supported by a result that HI is a conservative characteristic among soybean cultivar including determinate and indeterminate types (Spaeth et al, 1984). There was no difference in the response of HI to different light intercept conditions during the seedfi lling period among soybeans with different growth habits, unless dry matter production during the seedfi lling period is strongly suppressed.…”
Section: Harvest Index (Hi)supporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, HI may be stable except when the assimilate during the seed-fi lling period is strongly suppressed by low solar radiation in all cultivars used. Our results were supported by a result that HI is a conservative characteristic among soybean cultivar including determinate and indeterminate types (Spaeth et al, 1984). There was no difference in the response of HI to different light intercept conditions during the seedfi lling period among soybeans with different growth habits, unless dry matter production during the seedfi lling period is strongly suppressed.…”
Section: Harvest Index (Hi)supporting
confidence: 86%
“…HI in soybean has been considered to be invariable irrespective of growth habit (Spaeth et al, 1984). However, when plants suffer from water (Schapaugh and Wilcox, 1980) or shading (Kakiuchi and Kobata, 2004) stress during the seed-fi lling period, the percentage of the dry weight before the fl owering stage to that of the fi nal plant dry weight becomes higher reducing HI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This Harvest Index range fell within the range (i.e. 0.37-0.45) reported by Rao et al (2002) and that reported by Spaeth et al (1984; Harvest Index range 0.25-0.6)). The estimated average root:shoot ratio soybean at harvest was 0.18.…”
Section: Sibcrop Simulations For Summer Crops (Maize and Soybean)supporting
confidence: 82%
“…4 and 8). Although harvest index in soybeans is unstable when shoot dry matter at maturity is markedly low, it is stable in many cases, including interplant competition, photoperiod, the timing of drought stress, irrigation rate, and planting density or shading conditions (Spaeth et al, 1984;Kakiuchi and Kobata, 2004). Our results under various P conditions are in agreement with these reports.…”
Section: Discussionsupporting
confidence: 91%